The induction of bone formation by 3D-printed PLGA microsphere scaffolds in a calvarial orthotopic mouse model: a pilot study - Klar, Roland M.; Cox, James C.; Houchen, Claire J.; Raja, Naren; Bouloussa, Houssam; Lohfeld, Stefan (Frontiers in Bioengineering and Biotechnology, 2024)
Polymeric biodegradable microspheres are readily utilized to support targeted drug delivery for various diseases clinically. 3D printed tissue engineering scaffolds from polymer filaments with embedded microspheres or nanoparticles, as well as bulk microsphere scaffolds, have been investigated for regenerative medicine and tissue engineering. However, 3D printed scaffolds consisting only of a homogenous microsphere size with an optimized architecture that includes a unique micro-and macroporosity, have been challenging to produce and hence, have not been assessed in the literature yet. Utilizing our recently established 3D-MultiCompositional Microsphere-Adaptive Printing (3D-McMap) method, the present study evaluated the effectiveness of 3D-printed poly(lactic-co-glycolic acid) (PLGA) microsphere scaffolds, consisting of microsphere sizes 50, 100, or 200 µm, on the induction of bone formation when implanted in the calvarial murine regeneration model. Our results showed that PLGA microsphere scaffolds possess unique properties that support bone regeneration by supporting osteoconduction and stimulating, in our opinion, true spontaneous osteoinduction. The study demonstrated that PLGA microsphere-based scaffolds support bone growth in the absence of additional growth factors and promote osteogenesis primarily via their unique geometric configuration. The larger the microspheres were, the greater de novo bone formation was. This proves that bone tissue engineering scaffolds 3D printed from microspheres, enabled by the 3D-McMap method, are superior over bulk material printed scaffolds, as they possess the unique capability of spontaneous induction of new bone formation. With the addition of encapsulated modulatory bone-forming biomolecules they can substantially improve the spatiotemporal control of tissue morphogenesis, potentially leading to new innovative clinical tissue repair therapies that regenerate bone in large defects correctly and fully.